60 - NURSING AND ROY´S THEORETICAL MODEL OF ADAPTATION: AN INTEGRATIVE REVIEW (Fiep Bulletin - online, 2011)
ABSTRACT: The goal of the present study is to identify, in the literature, the application trend of Roy's AdaptationTheory in nursing, specifically the focus of the application experiences in Latin America. The study is an integrated review of the publications indexed in data bases SCIELO, LILACS, ADOLEC, and BDENF, of the Virtual Library of Health that focuses on health literature of Latin America and the Caribbean. The study was conducted during the months of June and July 2008, using the descriptor “Roy´s theory” and the inclusion criteria that the publication date be during the period 1984-2008, that the focus be on the theory,   and that the complete text be available for analysis. The sample that comprised the study consisted of 32 publications selected from the 66 documents initially found. Results indicate that the number of publications relating to the theory increased significantly after 1999. The majority of the studies were conducted by nursing practitioners with PhD, were research studies with a focus on diverse populations and on various problems. However,  more frequently in research relating to women's health and surgical health care.  We conclude that in keeping with purpose of the Roy´s nursing  theory which is to focus on assisting the adaptation  of the individual to the stimuli presented by his health/illness condition, the publications have centered on the search for knowledge of its application with different populations, rather than on the effectiveness of the theory. It is necessary, therefore, the theory be more divulged among nurse practitioners and that studies be conducted that evaluate the results on the improvement of care in the recipients.